2007
DOI: 10.1146/annurev.neuro.30.051606.094328
|View full text |Cite
|
Sign up to set email alerts
|

The Medial Temporal Lobe and Recognition Memory

Abstract: The ability to recognize a previously experienced stimulus is supported by two processes: recollection of the stimulus in the context of other information associated with the experience, and a sense of familiarity with the features of the stimulus. Although familiarity and recollection are functionally distinct, there is considerable debate about how these kinds of memory are supported by regions in the medial temporal lobes (MTL). Here, we review evidence for the distinction between recollection and familiari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

267
2,203
27
21

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 2,316 publications
(2,518 citation statements)
references
References 177 publications
267
2,203
27
21
Order By: Relevance
“…Ennaceur and Delacour (1988) propose that the strength of this task is that it reflects spontaneous behaviour in the animal, therefore it is a ''pure'' memory test without the need for any rule learning and as such, it is easily comparable across species. Recently, there have been a number of comprehensive reviews of the object recognition task and in particular we refer the reader to reviews on the one trial object recognition task (Dere et al, 2007) and on the neural substrates underlying recognition memory (Eichenbaum et al, 2007;Brown et al, 2010;Clark and Squire, 2010;Warburton and Brown, 2010).…”
Section: Object Recognition Memorymentioning
confidence: 99%
“…Ennaceur and Delacour (1988) propose that the strength of this task is that it reflects spontaneous behaviour in the animal, therefore it is a ''pure'' memory test without the need for any rule learning and as such, it is easily comparable across species. Recently, there have been a number of comprehensive reviews of the object recognition task and in particular we refer the reader to reviews on the one trial object recognition task (Dere et al, 2007) and on the neural substrates underlying recognition memory (Eichenbaum et al, 2007;Brown et al, 2010;Clark and Squire, 2010;Warburton and Brown, 2010).…”
Section: Object Recognition Memorymentioning
confidence: 99%
“…Others have emphasized that different MTL structures play separate roles in declarative memory as well as in other cognitive functions such as higher-order visual perception Graham and Gaffan, 2005), working memory (Axmacher et al, 2007;Piccioni et al, 2007;Olson et al, 2006a,b), and short-term memory (Piekema et al, 2006). It has been suggested that, during encoding, visual object features are processed in the perirhinal and lateral entorhinal cortex, while spatial context is processed in the adjacent medial entorhinal cortex and parahippocampal cortex (Eichenbaum et al, 2007). Indeed, lesions to the perirhinal cortex alone, or together with the entorhinal cortex, have been shown to cause significant deficits in the ability of humans (Barense et al, 2005), monkeys (Baxter and Murray, 2001) and rats (Prusky et al, 2004) to perform visual categorization and memory tasks, deficits not found when lesions are restricted to the hippocampus.…”
Section: Introductionmentioning
confidence: 99%
“…It is now widely accepted that recognition memory is underpinned by two neurocognitive processes, namely 'recollection' and 'familiarity' (for reviews see Yonelinas 2002;Eichenbaum et al 2007;Mandler 2008). In this context, recollection can be defined as memory for an event with retrieval of accompanying spatiotemporal contextual details, whereas familiarity does not involve this degree of episodic richness (Tulving 1985;Aggleton and Brown 2006).…”
mentioning
confidence: 99%
“…In this context, recollection can be defined as memory for an event with retrieval of accompanying spatiotemporal contextual details, whereas familiarity does not involve this degree of episodic richness (Tulving 1985;Aggleton and Brown 2006). It has been proposed that recollection is mediated by the hippocampus; by contrast, familiarity is thought to be subserved by the perirhinal cortex (Brown and Aggleton 2001;Aggleton and Brown 2006;Eichenbaum et al 2007; but see Squire et al 2007 for a conflicting view). The basis of this neuroanatomical distinction is largely predicated upon a series of hippocampal amnesic cases in which familiarity processes are relatively spared in the context of recollection deficits (e.g.…”
mentioning
confidence: 99%